SHIFTING CORRELATION STRUCTURES IN FINANCIAL MARKETS: GOLD, OIL, EQUITIES, AND BITCOIN - Pirnazarov Ernazar Dauletiyarovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The increasing integration of global economies has strengthened the interdependence of financial markets. Shocks originating in one sector or region often transmit rapidly across borders, influencing asset prices and investor sentiment worldwide. This phenomenon has been particularly evident during major financial crises, when investors simultaneously reallocate their portfolios across equities, bonds, commodities, and alternative assets such as cryptocurrencies. Understanding correlations between financial markets is therefore of crucial importance for policymakers, institutional investors, and private traders. The aim of this study is to analyze the nature and strength of correlations between key financial markets, with a special focus on gold, the U.S. dollar index (DXY), crude oil, stock market indices (S&P 500, Nasdaq), and Bitcoin. The period of analysis covers 2015–2025, which allows the inclusion of several important macroeconomic shocks, including the 2015–2016 oil crisis, the COVID-19 pandemic, and the subsequent recovery marked by monetary tightening in 2022–2023. The objectives of this article are threefold: To define and conceptualize correlation in financial theory. To empirically evaluate the correlations between selected financial instruments. To discuss the implications of these relationships for risk management and investment strategies. Financial markets, correlation, gold, U.S. dollar, oil, S&P 500, Nasdaq, Bitcoin, diversification, risk management